2016
DOI: 10.1002/ijc.30137
|View full text |Cite
|
Sign up to set email alerts
|

A novel EGR‐1 dependent mechanism for YB‐1 modulation of paclitaxel response in a triple negative breast cancer cell line

Abstract: Chemotherapy with taxanes such as paclitaxel (PTX) is a key component of triple negative breast cancer (TNBC) treatment. PTX is used in combination with other drugs in both the adjuvant setting and in advanced breast cancer. Because a proportion of patients respond poorly to PTX or relapse after its use, a greater understanding of the mechanisms conferring resistance to PTX is required. One protein shown to be involved in drug resistance is Y-box binding protein 1 (YB-1). High levels of YB-1 have previously be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…The following are the four members of this family: EGR1, EGR2, EGR3 and EGR4. All of these TFs have been proven to correlate with breast cancer pathogenesis and prognosis [2528]. In addition, this study found the following tissue specific TFs that were not reported in breast cancer: ATOH8, DMRT2, TBX15 and ZNF367.…”
Section: Discussionmentioning
confidence: 62%
“…The following are the four members of this family: EGR1, EGR2, EGR3 and EGR4. All of these TFs have been proven to correlate with breast cancer pathogenesis and prognosis [2528]. In addition, this study found the following tissue specific TFs that were not reported in breast cancer: ATOH8, DMRT2, TBX15 and ZNF367.…”
Section: Discussionmentioning
confidence: 62%
“…Herein, our data show that restoring miR-137 expression in BC cells led to the suppression of DUSP4 expression. DUSP4 upregulation has been reported in relation to drug resistance and patient outcome in BC [42][43][44] . Silencing DUSP4 significantly sensitized BC cells to trastuzumab 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous human tumor types, the clinical significance of YBX1 has been most extensively studied in breast cancer (Table , Doc ). Enhanced expression of YBX1 is predictive of poor outcomes in patients with breast cancer . Adjuvant endocrine therapy and chemotherapy treatments have been used extensively in the treatment of breast cancer .…”
Section: Y‐box Binding Protein‐1 Is An Effective Potent Target In Ovementioning
confidence: 99%
“…Enhanced expression of YBX1 is predictive of poor outcomes in patients with breast cancer. [36][37][38][39][40][41] Adjuvant endocrine therapy and chemotherapy treatments have been used extensively in the treatment of breast cancer. 42,43 However, the emergence of refractory tumors is a major complication for breast cancer patients treated with adjuvant endocrine therapy.…”
Section: Y-boxb Ind Ingprotein -1 Isaneffec Tivep Otenttarg E T Inomentioning
confidence: 99%